Association between reproductive behaviour and androgen metabolite excretion in free-ranging male giraffes (Giraffa camelopardalis) - Ganswindt, Andre (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2012.